The role of cosmopolitan orientation in COVID-19-related attitudes: perceived threats and opportunities, vaccination willingness, and support for collective containment efforts - Leung, Angela K.-y; Koh, Brandon; Lua, Verity Y. Q.; Liu, James H.; Choi, Sarah Y.; Lee, I-Ching; Lee, Michelle; Lin, Mei Hua *; Hodgetts, Darrin; Chen, Sylvia Xiaohua (Springer Verlag (Germany), 2023)
Cosmopolitan individuals identify themselves as “citizens of the world.” In the present research, we tested the idea that endorsing a cosmopolitan orientation (CO) is adaptive in the COVID-19 crisis. Cosmopolitan individuals more readily transcend national parochialism, show greater concern for all humanity, and prioritize collective interests. In a two-wave multi-region investigation with six samples from China, Hong Kong, Taiwan, Malaysia, Singapore, and the U.S., we first established longitudinal and cross-cultural measurement invariance of the CO scale. Next, we found that people with a higher CO tended to perceive over time a greater threat posed by COVID-19, take more safety measures, advocate collaboration to contain the pandemic and see opportunities for positive change brought about by COVID-19 (e.g., environmental sustainability). Higher CO was also associated with a greater willingness to be vaccinated and a greater support for collective containment efforts. Analyses also revealed these effects to be largely generalizable across regions, thus lending strong support for the pancultural function of CO in promoting the resilience of humanity in the trying times of the COVID-19 crisis. The materials, raw dataset, and analytic code for the current study are available at https://osf.io/pqvut/?view_only=e2419d8c26534fc19e6f91433fdbfeed.